Efek Serbuk Eestrak Etanol Kelopak Bunga Rosella (Hibiscus sabdariffa L.) Terhadap Jumlah Sel CD4 Pada Sukarelawan Sehat - Dini Mardhiyani; Endang Darmawan; Akrom Akrom (JURNAL ILMU KEFARMASIAN INDONESIA, 2018)
Roselle flower (Hibiscus sabdariffa L.) is beneficial as an immunostimulant because of its antioxidant property. Antioxidants in roselle flower are hibiscus anthocyanin, quercetin, L-ascorbic acid and protocatechuic acid. Any potential plants for pytopharmacy should be proven beneficial and safe through preclinical and clinical trial. The purpose of this clinical trial was to determine the effect of ethanol extract of roselle (Hibiscus sabdariffa L.) to lymphocyte and CD4 cell count in healthy volunteer for 30 days. This study used pre-post treatment design. A total of 21 healthy volunteer were chosen according to inclusion and exclusion criteria and filled informed consent. Healthy volunteer were given 500 mg roselle ethanol extract powder every day for 30 days. Lymphocyte and CD4 cell count was conducted using hematology analyzer and flowcytometer. Results were analyzed using paired t test, if the distribution is not normal than Wilcoxon test will be used on 95% confidence interval. Results showed that there was no significant effect (p>0,05) of CD4 cell absolute count and there was a significant effect of CD4 percentage (p<0,05). Results on day 45 (14 days after the treatment was interrupted) showed no significant effect (p>0,05) of CD4 cell absolute count and CD4 cell percentage. The effect of CD4 cell percentage on day 31 was in normal range. This study concluded that 500 mg roselle petal ethanol extract powder (Hibiscus sabdariffa L.) given everyday for 30 days showed some effect on d increasing CD4 cell percentage.